The role of Wilm’s Tumor1 immunohistochemical marker in surface epithelial ovarian tumors - AL Hafedh, Muna I.; Ali, Sahira A.; Talal, Lubab F. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: Wilms’ tumor 1 is a tumor suppressor gene. The gene is located in chromosome 11p13. And its expression was found in many solid tumors (including ovarian tumor) and also expressed in hematologic malignancies, Recent studies found that WT1 to be involved in angiogenesis.Objectives: To evaluate the expression of WT1 in surface epithelial ovarian tumorand study the possibility of using WT1 as replacement of both;ovarian tumor marker CA125 and a endothelial cell phenotypic marker CD34.Patients and methods: This is a study of a retrospective ( cross sectional ) of sixty cases with total abdominal hysterectomy and bilateral salpingo - oopherectomy collected from department of Histopathology – Teaching Laboratories / Medical City Teaching Hospital , as well as Al alwya hospital and Al Habibia hospital in Baghdad during the period of study from December 2007 to December 2012. Thirty cases diagnosed as surface epithelial ovarian tumors and thirty cases of histologically normal ovarian tissue which were included as a control group. Formalin - fixed, paraffin - embedded ovarian tissue blocks from 60 cases were used . Three section of 4 micron for each taken and stained with WT1, CD34, and CA125 immunohistochemical marker on positively charged slides.Results: there were a significant correlation between expression of WT1 and histological types of surface epithelial ovarian tumor with a higher expression in serous tumors among other cancer types (P-value < 0.001).There was a significant positive correlation between the expression of WT1 and CA125 scores ( p-value < 0.001).There was a significant correlation between WT1microvessel density (MVD) expression and CD34- microvessel density (MVD) expression in ovarian tumors (P-value = 0.05).On the other hand, there were no significant correlation of WT1 with the age of cases (P-value = 0.9) and with the grade of ovarian tumors ( P-value = 0.23) .Conclusions: The present study demonstrates high expression of WT1 in both tumor and endothelial cells in surface epithelial ovarian tumors, and it had dual usages in evaluation of both ovarian tumor cells and the vascular density. That was proved by demonstrating a significant correlation between WT1 and CA125 expression, and between WT1-MVD and CD34- MVD . There was no statistically significant association between WT1 expression and different tumor grades. There was significance differences in WT1expression among different histological subtypes of primary ovarian carcinomas, with serous carcinoma as the most frequent type.